2020
DOI: 10.1016/j.neulet.2020.135293
|View full text |Cite
|
Sign up to set email alerts
|

Eye blink rate increases as a function of cognitive load during an auditory oddball paradigm

Abstract: Previous evidence suggests that changes in spontaneous eye blink rate (EBR) in human adults might reflect the amount of attentional demand (i.e. cognitive load) during cognitive tasks. However, the actual direction of this relation is uncertain, since most studies investigated the role of cognitive load on EBR by employing visual tasks only. Here we aimed at elucidating the relationship between EBR and cognitive load in non-visual tasks.Sixteen healthy participants performed two auditory oddball tasks, i.e. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 63 publications
3
17
0
Order By: Relevance
“…One reason we may have seen a decrease in the Number of Fixations during the Math Task, was that the number of blinks increased. The increase in Blink Rate is consistent with findings from Magliacano et al ( 2020 ) where they found an increase in Blink Rate accompanying an auditory counting task with the absence of any visual task. Increased Blink Rate has also been found to coincide with visual scenes that require less attention and blinks are suppressed to reduce the chance of missing important information when visual attention is in demand (Nakano et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One reason we may have seen a decrease in the Number of Fixations during the Math Task, was that the number of blinks increased. The increase in Blink Rate is consistent with findings from Magliacano et al ( 2020 ) where they found an increase in Blink Rate accompanying an auditory counting task with the absence of any visual task. Increased Blink Rate has also been found to coincide with visual scenes that require less attention and blinks are suppressed to reduce the chance of missing important information when visual attention is in demand (Nakano et al, 2009 ).…”
Section: Discussionsupporting
confidence: 91%
“…The change in subjects' eye movement behavior are consistent with previous work showing a tendency to give attentional preference to auditory stimuli, potentially at the cost of one's visual processing capabilities (Robinson and Sloutsky, 2010 ; Dunifon et al, 2016 ) and an increase in Blink Rate (Magliacano et al, 2020 ). Neurophysiological work with EEG has shown that when auditory stimuli are paired with a visual task (cross-modal processing) there is a latency in the visual P300 response but no negative impact on the processing of auditory stimuli (Robinson et al, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
“…Even if the use of blink parameters is affected by strong variability both within and between subjects, in the current work a decrease of eye blink rate in the high condition has been observed, coherent with the literature, which associates this decrement with an increase in information processing [ 30 , 34 ]. However, the cognitive demand is not the only intrinsic factor affecting eye blink parameters: differences in visual load can induce an unexpected variation in both eye blink rate and duration [ 68 ]. Therefore, because for our experimental design we assumed (according to [ 28 ]) a comparable visual load between high and low conditions, we hypothesized that there was not enough of a difference between the conditions to induce a significant modulation in eye blink duration.…”
Section: Discussionmentioning
confidence: 99%
“…Eye tracking, apart from its aforementioned use in determining what users look at, also yields a measure for pupil dilation (associated with emotional arousal and cognitive effort [2,21]) and eye openness (a marker for drowsiness [16]). In addition, these raw data streams can be used to determine blink rate, which has also been identified as a marker of cognitive load [15,29]).…”
Section: Controlling the Product Testing Experience And Initiation Of Interactionsmentioning
confidence: 99%